Relationship among employees' emotional intelligence, rganizational performance and organizational culture at Shahid Beheshti University of Medical Sciences - Darvish, hassan; Shabani, fatemeh; Abedsaeedi, zhila (Advances in Nursing & Midwifery, 2015)
Abstract -------------------------------------------------------------------------------------------------------------------------------- Background and Objectives: Employees' emotional intelligence and a strong organizational culture, contributes to selecting appropriate strategies and improvement of organizational performance. The purpose of this study was to investigate the relationship among emotional intelligence, organizational performance and organizational culture of managers and staff in faculties of Shahid Beheshti University of Medical Sciences. Materials and Methods: This was a correlational research, assessing the relationship among emotional intelligence, organizational culture and performance. The sample of the study consisted of 200 managers and employees' serving in faculties of Shahid Beheshti University of Medical Sciences, Tehran, Iran. Participants were included in the study by stratified sampling method. Data were collected by a questionnaire which consisted of four sections: demographic information , emotional intelligence , organizational culture , and organizational performance. The reliability of the questionnaire was determined by computing Cronbach's alpha. Data wer analysed by Pearson test and SPSS and LISLER software . findings: 76.2 % of the respondents were female , 79.5 % of them aged 25 to 40 years, the educational level of 65.5 % of respondents were bachelor, 29% master and 5/5 percent PhD. The scores for emotional intelligence, organizational performance and organizational culture were (3.51 ±0.348),(4.03±0.494) and (2.99±0.649) respectively. There was a significant correlation between emotional intelligence scores and organizational culture (r=0.364 P=0.0001) , emotional intelligence and organizational performance ( r= 0.606 P=0.0001) and organizational culture and performance( r= 0.363 P= 0.001) . Conclusion: The results indicate that there is a significant correlation among emotional intelligence and organizational performance and organizational culture in a sample of employees' in faculties of Shahid Beheshti University of Medical Sciences. Keywords: emotional intelligence, enterprise performance, corporate culture